Studi Mikrotremor dengan Metode Horizontal to Vertical Spectral Ratio (HVSR) di Tapak RDE, Serpong - Iswanto, Eko Rudi; Indrawati, Yuni; Riyanto, Theo Alvin (EKSPLORIUM, 2019)
Natural disaster like earthquake can cause damage to the site and the infrastructure including nuclear reactor facilities. This phenomenon needs comprehensively understood through its dynamic characteristics historical records of the site. The use of Horizontal to Vertical Spectral Ratio (HVSR) method has been widely used for subsurface investigation since last decade. The aimed of the research is to obtain local geological and subsurface dynamic characetristics. This research is applying the use of HVSR method for Experimental Power Reactor (RDE) in Serpong. The measurements are in 15 locations, and then the data is processed by using Geopsy software. The analysis result shows that the RDE site has dominant frequncy values between 3.06 Hz–23.271 Hz and amplification factor 1.84–6.37. The northeast and southeast areas of the site have higher seismic vulnerability index than in other area. Therefore, the selection for reactor bulding location in the southwest area is proper because it has lower amplification factor, sedimen thickness, and seismic vulnerability index.